3Rs for innovating novel antibiotics: sharing resources, risks, and rewards. (3rd April 2012) - So, Anthony D; Ruiz-Esparza, Quentin; Gupta, Neha; Cars, Otto
Abstract : The stream of new antibiotics is struggling to keep up with emerging bacterial resistance. Anthony So and colleagues examine what can be done to increase innovation